ANALISIS TINGKAT PELAYANAN INTEGRASI ANTARMODA BERDASARKAN PERSEPSI PENGGUNA KRL DI STASIUN MANGGARAI - Akbar Danindra Montana; Yenita (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
This study aims to assess the level of intermodal integration services in the Manggarai Station KRL service according to the user's perception. This study uses descriptive analysis techniques with quantitative CSI and IPA methods obtained from variables that have been adjusted into 5 dimensions of service quality. From this study it shows that the results of KRL services on intermodal integration in the Manggarai Region have fulfilled the satisfaction category in the user satisfaction level of 70.1%. However, there are still services that do not meet categories such as the distance from Manggarai Station to other modes of transportation and the ease of KRL users changing modes of transportation.